Information and power: Women of color's experiences interacting with health care providers in pregnancy and birth - Altman, Molly R.; Oseguera, Talita; McLemore, Monica R.; Kantrowitz-Gordon, Ira; Franck, Linda S.; Lyndon, Audrey (Social science & medicine (1982), 2019)
Preterm birth and other poor birth outcomes disproportionately affect women of color. Emerging evidence suggests that socially-driven issues such as disrespect, abuse, and discrimination within the health care system influence how people of color experience care during pregnancy, birth, and postpartum, which contributes to poorer outcomes for the mother and baby. As recommended by community partners, we explored how interactions with providers were perceived and understood in the context of seeking care for pregnancy and birth. For this constructivist grounded theory study, we recruited 22 self-identified women of color 18 years of age or older and who were between six weeks and one year postpartum. Women participated in interviews exploring their experiences, which were audiorecorded and transcribed. Data were analyzed using dimensional analysis and situational analysis methods. The concepts of information and power surfaced in analysis, in which providers have control over the information they share and “package” information to exert power over women's ability to participate in decision-making. An established relationship with providers and acknowledged levels of privilege or marginalization influenced how information was shared. Contextual factors included provider bias and judgment towards their patients, health care system structural issues, and the overall power dynamic between patient and provider. Women of color's experiences during pregnancy and birth were influenced by how they were treated by providers, particularly in how information was shared and withheld. The providers' control over information led to a power dynamic that diminished women's ability to maintain autonomy and make health care decisions for themselves and their children. This study provides insight and impetus for change in how providers share information, utilize informed consent, and provide respectful care to women of color during pregnancy and birth care. •Information packaging by providers influenced women of color's experiences.•Providers' control over information influences autonomy and decision-making.•Respectful care involves providers recognizing their power in patient interactions.